Gamifikasi Bahasa Arab Dengan Model Blended Learning - Lutfiyatun, Eka (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2021)
Learning Arabic in Indonesia is entering a new phase in line with the ongoing pandemic. Schools are allowed to hold limited face-to-face meetings with reduced class hours. In response to this, a blended learning model is applied by combining face-to-face learning models in class and at other times conducting online learning outside the classroom or at home. To help students achieve the objectives of learning Arabic, there are alternative technology-based learning methods, namely in the form of gamification by utilizing online or android-based games. The purpose of this study is to describe how educators apply gamification in blended learning. The method used in writing this article is a literature review that produces descriptive data from various research results on teacher experiences in gamification in blended learning. The results of the study show that various types of Arabic learning games have been developed and used by educators. The game allows students to practice language with a fun experience. This provides convenience and increases interest for students, so that learning objectives can be more effectively realized.